The Development of Piano Class to Enhance Playing and Singing Ability for Preschool Education Majors - Wan, Wenjie; Phokha, Pramote; Chiangthong, Nut (Journal of Ecohumanism, 2025)
The purpose of this study is to evaluate the influence of different teaching methods on the piano ability of students majoring in preschool education scientifically and to demonstrate the new collective piano playing and singing course and its curriculum Specific objectives aim to study the current situation and needs of piano teaching for preschool education majors and present a new piano course aimed at improving students’ playing and singing ability. This paper studies the current situation and needs of piano teaching in preschool education majors in higher vocational colleges through literature and questionnaire survey In order to achieve the second goal, the research based on the subject-centered theory and Taylor goal combined with Fink integrated curriculum design, designed a new piano playing and singing collective curriculum. The research adopts quasi-experimental design to conduct empirical research on the new curriculum, collects data through interviews, measurements and contents. The findings reveal that the new curriculum combined with Fink has significantly improved students’ piano playing and singing ability and music literacy, enhanced their practical teaching and performance ability, and improved the overall learning effect through scientific evaluation and feedback mechanism. The research conclusion emphasizes that the curriculum design should choose and organize effective learning based on clear educational goals and improve teaching practice through scientific evaluation, so as to comprehensively improve the teaching and students’ learning effect of piano playing and singing course in preschool education.